Methodology for Assessing and Implementing Financial Technologies in Kazakhstan - Zh. S. Almabekova; G. N. Jaxybekova (Экономика: стратегия и практика, 2025)
In the context of the rapid digital transformation of Kazakhstan’s economy, financial technologies (FinTech) have become a key factor in modernizing the financial sector. The study aims to develop a comprehensive methodology for assessing and implementing FinTech in Kazakhstan’s financial sector, as well as analyzing their impact on economic performance and operational efficiency. The research methodology includes theoretical and methodological analysis, regression modeling, SWOT analysis, content analysis, as well as methods of quantitative and qualitative assessment: paired t-test and analysis of variance (ANOVA). The initial data is based on statistics from the Kazakh fintech industry, the results of a survey of 2000 respondents, and operational and financial indicators from Kaspi Bank. The results indicate a significant impact of FinTech, including a 30% reduction in transaction costs, an increase in non-cash payment share from 45% to 83%, an increase of more than 200% in the number of active mobile banking users, and an increase from 52 points to 78 in satisfaction levels. Regression analysis showed a significant impact of factors such as investments in fintech (β = 0.28, p < 0.01) and the level of transaction security (β = 0.31, p < 0.05) on operational efficiency. These results demonstrate that financial technologies lead to increased business efficiency, greater access to financial services, and faster digital transformation. Future research may be aimed at assessing the impact of new technologies, such as blockchain and artificial intelligence, on the financial sector’s sustainability, the development of regulatory mechanisms, and the increasing digital inclusion of various population groups.